Graphene grafted hydroxyl glycidyl azide ether and obtained energetic polyurethane elastomer
Through alkynylated graphene oxide and click chemical grafting technology, the problems of poor dispersion and weak interface binding force in polymer matrix are solved, which significantly improves the mechanical properties of composite materials and is suitable for continuous processing and special environmental applications.
Patent Information
- Application Number
- CN202411913706.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-01
AI Technical Summary
The poor dispersion of graphene in polymer matrix and weak interface binding force leads to poor modification effect on polymer composite materials, and traditional composite processes have problems such as high cost, environmental pollution and inconsistent performance.
Graphene grafted hydroxy azide ether is prepared by alkyning the graphene oxide and grafting it with low molecular weight terminal hydroxy azide glycidyl ether as a nanohybridization reaction plasticizer for the composite of GAP polyurethane elastomer.
The dispersion and interface bonding force of graphene in the polyurethane matrix are significantly improved, the mechanical properties of the composite material are improved, the hardness is increased by 35.1%, the tensile strength is increased by 106.0%, and the 50% fixed-extension stress is increased by 172.4%, and it meets the needs of continuous processing and production.
Smart Images

Figure CN119735521A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of graphene oxide modification and graft polymerization, and in particular relates to a graphene grafted hydroxyl azide glycidyl ether and an obtained energetic polyurethane elastomer. Background Art
[0002] Glycidyl azide polyether (GAP) and its composites have broad application prospects due to their high energy density, good mechanical properties and thermal stability. In particular, their application in solid propellants is particularly important. By compounding GAP with other components, the performance of the propellant can be effectively improved, providing higher thrust and better combustion efficiency. Inorganic or organic fillers are usually required to be added to GAP composites to enhance their mechanical properties and thermal stability. However, since the main chain of the GAP molecule contains a large amount of azidomethyl groups, the low mechanical properties of the prepared GAP polyurethane film are the main technical difficulties that lead to the poor mechanical properties of the high-energy propellant composites prepared therefrom. Therefore, how to improve the mechanical properties of GAP polyurethane film is the key core technology for preparing high-performance propellant composites.
[0003] As a two-dimensional material, graphene has received great attention in the field of composites with polymers due to its unique structure. In recent years, the problem of uneven dispersion of graphene in the polymer matrix has not been well solved. The poor dispersion of graphene in the polymer matrix and the weak interface bonding weaken the composite effect of graphene on the polymer. At present, chemical modification of the surface oxygen-containing functional groups of graphene, especially alkyne modification, is a way to improve its dispersibility and interface bonding in the polymer matrix and improve the composite effect on the polymer matrix. However, there is still a lack of effective modification methods for alkyne modification of graphene and then effective composite modification of azide high-energy polyurethane propellant.
[0004] When traditional carbon materials are compounded with polyurethane, they are easy to agglomerate due to their high surface energy. This agglomeration phenomenon will cause uneven distribution of carbon materials in polyurethane, making it impossible to effectively improve the performance of the composite material. Some traditional compounding processes, such as solution blending, require a large amount of organic solvents to dissolve polyurethane and disperse carbon materials. This not only increases production costs, but also brings environmental pollution and safety hazards. Therefore, the traditional compounding process is affected by many factors, and it is difficult to ensure the consistency of the compounding of carbon materials and polyurethane in the production process of different batches. Summary of the invention
[0005] The invention provides a graphene-grafted hydroxyl azide glycidyl ether and the obtained energetic polyurethane elastomer, aiming to solve the problem of poor dispersion of graphene in a matrix and prepare a graphene polyurethane composite material with high mechanical properties. The method meets the needs of continuous processing and production and is suitable for promotion and application in special service environments.
[0006] In order to achieve the above object, the present invention provides a method for preparing alkyne-containing graphene oxide, comprising the following steps:
[0007] Ultrasonic dispersion of the carbon material and dimethylformamide (DMF) to obtain a dispersion;
[0008] The obtained dispersion liquid was added dropwise with thionyl chloride while stirring, heated in an oil bath, centrifuged after the reaction, washed and dried to obtain Cl-GO;
[0009] Cl-GO was dispersed with DMF, and acetylenic reactant, dichloromethane and triethylamine were added. After oil bath reaction, centrifugation was performed, and the mixture was washed and dried to obtain acetylenic graphene oxide A-GO. Figure 1 shown.
[0010] Preferably, in the preparation of Cl-GO:
[0011] The carbon material used is selected from one of graphene oxide and carbon nanotubes, preferably graphene oxide, and its carboxyl content is 5wt%;
[0012] The mass ratio of the added graphene oxide to dimethylformamide is 1:100-1:500, preferably 1:300;
[0013] The oil bath heating temperature is 50-90°C, and the reaction time is 18-26h; preferably, the reaction is carried out at 65°C for 24h;
[0014] The drying temperature is 80-150° C., and the drying is carried out in a vacuum environment for 6-8 hours; preferably, the drying temperature is 150° C., and the drying is carried out in a vacuum environment for 8 hours.
[0015] Preferably, in the preparation of A-GO:
[0016] The alkynyl reactant is selected from any one of pentynol, propynol, and propargylamine; preferably propargylamine;
[0017] The volume ratio of acetylation reactants: dichloromethane: triethylamine is 1:2:1;
[0018] The oil bath reaction temperature is 25-60°C, and the reaction time is 4-12h; preferably, the reaction is carried out at 50°C for 5h.
[0019] As a preferred embodiment, according to infrared spectroscopy, the alkyne-modified graphene oxide has a wavelength of 2100-2200 cm -1 A sharp alkynyl characteristic peak appears at the surface, and the dispersion stability test shows that the dispersion stability in DMF is higher than that of graphene oxide.
[0020] The present invention also provides a graphene-grafted hydroxyl azide glycidyl ether GO-g-GAP, which is prepared by click chemistry grafting of alkynylated graphene oxide prepared by any of the above technical solutions and hydroxyl azide glycidyl ether.
[0021] It can be understood that click chemistry is based on the efficient reaction between the highly active alkynyl functional groups of alkynylated graphene oxide and the azide group of terminal hydroxyl azide glycidyl ether, generating a stable triazole five-membered heterocycle to graft the graphene sheet particles with the flexible molecular main chain to form a highly dispersed graphene polymer masterbatch. As the graphene masterbatch participates in the curing reaction of polyurethane as a reactive plasticizer, a highly dispersed polyurethane / graphene oxide composite elastomer is formed.
[0022] Traditional alkyne-modified graphene oxide relies on weak van der Waals forces to achieve the composite of nanoparticles and polyurethane matrix, and the dispersion of graphene is not well solved. The present invention prepares a graphene polymer masterbatch by means of a click chemistry reaction, which grafts graphene oxide onto the main chain of an azide polyether by strong covalent bonds. It better solves the key technical problem of high dispersion of graphene and polyurethane matrix, which is an important inventive point of the present invention. In particular, the graphene masterbatch is grafted with low molecular weight terminal hydroxyl azide polyether, which is a homologue of the GAP family with large-weight terminal hydroxyl azide polyether. The present invention uses an azide graphene masterbatch (GO-g-GAP) for the first time for the composite modification of GAP polyurethane elastomers, which is used to solve the technical problem of low mechanical properties that plague the manufacturing field of azide high-energy propellants, which is another important inventive point of the present invention. Furthermore, the higher the content of graphene two-dimensional sheet particles in the polyurethane matrix, the better the modification effect. There is often an optimal dosage when nanoparticles are compounded. This optimal dosage not only saves costs but also has a better nano-modification effect. It is a common phenomenon in the field of nano-composite technology.
[0023] The present invention also provides a method for preparing the graphene-grafted hydroxyl azide glycidyl ether GO-g-GAP according to the above technical solution, comprising the following steps:
[0024] Ultrasonic dispersion of acetylated graphene oxide and dimethylformamide is performed to obtain a dispersion;
[0025] Add hydroxyl azide glycidyl ether and a catalyst to the dispersion, heat in an oil bath for reaction, and centrifuge and dry the reaction product to obtain graphene-grafted hydroxyl azide glycidyl ether GO-g-GAP. Figure 2 shown.
[0026] Preferably, the mass ratio of the added alkynylated graphene oxide to hydroxyl azide glycidyl ether is 1:10-1:40;
[0027] The relative molecular weight of hydroxyazide glycidyl ether is 800-1200, preferably 1100.
[0028] Preferably, the catalyst is selected from Cu +1 The substance is selected from any one of CuI, CuBr and CuCl;
[0029] The oil bath heating is preferably carried out at 60°C for 6 hours;
[0030] The drying temperature is 80°C and the drying time is 10 hours.
[0031] As a preferred embodiment, GO-g-GAP was characterized by infrared spectroscopy and transmission electron microscopy, and it can be directly seen that 1650cm -1 The generation of characteristic peaks of left and right triazole rings and the dispersion of acetylenic graphene oxide in the GAP matrix.
[0032] The present invention also provides a graphene oxide composite energetic polyurethane elastomer GAP / GO-ETPU, which is prepared by adding the GO-g-GAP described in the above technical scheme or the GO-g-GAP prepared by any of the above technical schemes as a reactive plasticizer into GAP.
[0033] The present invention also provides a method for preparing the graphene oxide composite energetic polyurethane elastomer GAP / GO-ETPU according to the above technical solution, comprising the following steps:
[0034] GO-g-GAP is added as a filler to hydroxyl azide glycidyl ether, and vacuum dehydration is performed. Toluene diisocyanate is added to the mixed system to react, and then a solvent is added to dilute the mixture. After the reaction is completed, a chain extender is added to react for 1-5 minutes to obtain a mixed solution.
[0035] The obtained mixed solution is dried and solidified to obtain GAP / GO-ETPU. Figure 3 shown.
[0036] Preferably, the mass ratio of the added GO-g-GAP and hydroxyazide glycidyl ether is 1:4;
[0037] The vacuum dehydration temperature is 75-105°C, and the dehydration time is 0.5-1.5h; the preferred dehydration temperature is 85°C, and the dehydration time is 1h;
[0038] The prepolymerization temperature is 75-80°C, and the reaction time is 1.5-2.5h; preferably, the prepolymerization temperature is 78°C, and the reaction time is 2h;
[0039] The solvent is 1-2-dichloroethane or DMF, preferably 1-2-dichloroethane, and the chain extender is dimethylthiotoluene diamine;
[0040] The drying temperature is 25°C-40°C, preferably 30°C.
[0041] Compared with the prior art, the advantages and positive effects of the present invention are:
[0042] 1. The present invention adopts a new reaction pathway to first prepare alkyne-modified graphene oxide, and then reacts with low molecular weight terminal hydroxyl azide glycidyl ether to produce a click chemistry reaction, thereby innovatively preparing azide graphene masterbatch (GO-g-GAP) in which graphene is chemically grafted to a flexible molecular backbone. This highly dispersed GO-g-GAP can be used as a nano-hybrid reactive plasticizer for the curing of GAP polyurethane elastomers, thereby preparing a new type of GAP energetic polyurethane elastomer (GO / GAP-ETPU) composited with graphene oxide.
[0043] 2. The preparation method of click chemistry grafted alkyne-modified graphene-hydroxyazide glycidyl ether (GAP) provided by the present invention can be carried out without harsh conditions, which not only saves energy consumption, but also improves its dispersion ability in the polyurethane matrix, helps it to exert the mechanical property enhancement effect of two-dimensional graphene on polyurethane composite materials, and is suitable for promotion and application in special environments.
[0044] 3. The GO-composite energetic polyurethane elastomer GAP / GO-ETPU provided by the present invention exhibits excellent mechanical properties compared with the control sample, with hardness increased by 35.1%, tensile strength increased by 106.0%, and 50% elongation stress increased by 172.4%, which provides an applied research basis for the preparation of high-performance and highly stable GAP-ETPU. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 The preparation principle of alkynylated graphene oxide provided by the embodiment of the present invention;
[0046] Figure 2 The preparation principle of GO-g-GAP provided in the embodiment of the present invention;
[0047] Figure 3 The preparation principle of GAP / GO-ETPU provided in the embodiment of the present invention;
[0048] Figure 4 Infrared spectra of GO and A-GO provided in the embodiments of the present invention;
[0049] Figure 5 Infrared spectra of GAP and GO-go-GAP provided in the embodiments of the present invention. DETAILED DESCRIPTION
[0050] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0051] If no specific conditions are specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If not otherwise specified, in the following embodiments, the reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.
[0052] Comparative Example 1
[0053] Untreated GO.
[0054] Example 1
[0055] Take 10mL DMF solution and 0.1g carboxylated graphene oxide, pour into a 50mL three-necked flask, and disperse it ultrasonically in a disperser for 1h to make it completely dispersed. Take another 4mL of thionyl chloride and slowly add it to the dispersed graphene oxide-DMF solution, and react in an 80℃ oil bath for 24h. After the reaction is completed, the product is centrifuged and washed and dried to obtain chlorinated graphene oxide. The chlorinated graphene oxide prepared above is placed in a round-bottom flask, DMF is added to the flask to form a mixed solution, and then propargylamine, dichloromethane, and triethylamine are added in sequence. The flask is treated with an ice-water bath. After the reaction in the system is stable, the flask is moved to a 50℃ oil bath and heated at a constant temperature for 5h. After the reaction is completed, the product is centrifuged and washed and then vacuum dried at 80℃ for 6h to obtain A-GO-1.
[0056] Example 2
[0057] Take 10mL DMF solution and 0.1g carboxylated graphene oxide, pour into a 50mL three-necked flask, and disperse it ultrasonically in a disperser for 1h to make it completely dispersed. Take another 4mL of thionyl chloride and slowly add it to the dispersed graphene oxide-DMF solution, and react in an 80℃ oil bath for 24h. After the reaction is completed, the product is centrifuged and washed and dried to obtain chlorinated graphene oxide. The chlorinated graphene oxide prepared above is placed in a round-bottom flask, DMF is added to the flask to form a mixed solution, and then pentynol, dichloromethane, and triethylamine are added in sequence. The flask is treated with an ice-water bath. After the reaction in the system is stable, the flask is moved to a 50℃ oil bath and heated at a constant temperature for 5h. After the reaction is completed, the product is centrifuged and washed and then vacuum dried at 80℃ for 6h to obtain A-GO-2.
[0058] Comparative Example 2
[0059] Ungrafted reaction of hydroxyl azide glycidyl ether (GAP).
[0060] Comparative Example 3
[0061] 0.05g A-GO was added to 70mL DMF for ultrasonic dispersion for 1h to form a mixed solution, and then 4g GAP and catalyst CuI were added, and the reactants were reacted in an oil bath at 60℃ for 6h. After the reaction, the product was centrifuged, and the supernatant was dried in a vacuum environment at 60℃ for 8h. GO-g-GAP oligomer was obtained, which was recorded as GO-g-GAP-1.
[0062] Comparative Example 4
[0063] 0.5 g A-GO was added to 70 mL DMF and ultrasonically dispersed for 1 h to form a mixed solution, and then 4 g GAP and catalyst CuI were added, and the reactants were reacted in an oil bath at 60 ° C for 6 h. After the reaction, the product was centrifuged, and the supernatant was dried in a vacuum environment at 60 ° C for 8 h. GO-g-GAP oligomer was obtained, which was recorded as GO-g-GAP-2.
[0064] Example 3
[0065] 0.1g A-GO was added to 70mL DMF and ultrasonically dispersed for 1h to form a mixed solution, and then 4g GAP and catalyst CuI were added, and the reactants were reacted in an oil bath at 60℃ for 6h. After the reaction, the product was centrifuged, and the supernatant was dried in a vacuum environment at 60℃ for 8h. GO-g-GAP oligomer was obtained, which was recorded as GO-g-GAP-3.
[0066] Example 4
[0067] 0.2g A-GO was added to 70mL DMF and ultrasonically dispersed for 1h to form a mixed solution, and then 4g GAP and catalyst CuI were added, and the reactants were reacted in an oil bath at 60℃ for 6h. After the reaction, the product was centrifuged, and the supernatant was dried in a vacuum environment at 60℃ for 8h. GO-g-GAP oligomer was obtained, which was recorded as GO-g-GAP-4.
[0068] Example 5
[0069] 0.3 g of A-GO was added to 70 mL of DMF and ultrasonically dispersed for 1 h to form a mixed solution, and then 4 g of GAP and catalyst CuI were added, and the reactants were reacted in an oil bath at 60 ° C for 6 h. After the reaction, the product was centrifuged, and the supernatant was dried in a vacuum environment at 60 ° C for 8 h. GO-g-GAP oligomer was obtained, which was recorded as GO-g-GAP-5.
[0070] Example 6
[0071] 0.4 g A-GO was added to 70 mL DMF and ultrasonically dispersed for 1 h to form a mixed solution, and then 4 g GAP and catalyst CuI were added, and the reactants were reacted in an oil bath at 60 ° C for 6 h. After the reaction, the product was centrifuged, and the supernatant was dried in a vacuum environment at 60 ° C for 8 h. GO-g-GAP oligomer was obtained, which was recorded as GO-g-GAP-6.
[0072] Comparative Example 5
[0073] GAP was mixed evenly with GAP polymer as a reactive hybrid plasticizer, vacuum dehydrated at 85℃×755mmHg for 1h, cooled to 60℃, and the measured TDI was slowly added to the GAP mixed system, reacted at 75℃ for 2h to form a GO-grafted prepolymer, and finally 1,2-dichloroethane was added to dilute to obtain a standby polyurethane prepolymer, and the chain extender DMTDA was added to the prepolymer and stirred for 2h to form a mixed solution. The prepared mixed solution was slowly poured into a tetrafluoroethylene plate mold, placed in a 30℃ oven, and dried for 12h to solidify into a GAP / GO-ETPU film, which was recorded as ETPU-0.
[0074] Comparative Example 6
[0075] 0.05g of A-GO and GAP grafted product GO-g-GAP-1 was mixed evenly with GAP polymer as a reactive hybrid plasticizer, vacuum dehydrated at 85℃×755mmHg for 1h, cooled to 60℃, and the measured TDI was slowly added to the GAP mixed system, reacted at 75℃ for 2h to form a GO grafted prepolymer, and finally 1,2-dichloroethane was added to dilute to obtain a standby polyurethane prepolymer, and the chain extender DMTDA was added to the prepolymer and stirred for 2h to form a mixed solution. The prepared mixed solution was slowly poured into a tetrafluoroethylene plate mold, placed in a 30℃ oven, and dried for 12h to solidify into a GAP / GO-ETPU film, which was recorded as ETPU-1.
[0076] Comparative Example 7
[0077] 0.5g of A-GO and GAP grafted product GO-g-GAP-2 were mixed evenly with GAP polymer as reactive hybrid plasticizers, vacuum dehydrated at 85℃×755mmHg for 1h, cooled to 60℃, and the measured TDI was slowly added to the GAP mixed system, reacted at 75℃ for 2h to form a GO grafted prepolymer, and finally 1,2-dichloroethane was added to dilute to obtain a standby polyurethane prepolymer, and the chain extender DMTDA was added to the prepolymer and stirred for 2h to form a mixed solution. The prepared mixed solution was slowly poured into a tetrafluoroethylene plate mold, placed in a 30℃ oven, and dried for 12h to solidify into a GAP / GO-ETPU film, which was recorded as ETPU-2.
[0078] Example 7
[0079] 0.1g A-GO and GAP grafted product GO-g-GAP-3 were mixed evenly with GAP polymer as reactive hybrid plasticizer, vacuum dehydrated at 85℃×755mmHg for 1h, cooled to 60℃, and the measured TDI was slowly added to the GAP mixed system, reacted at 75℃ for 2h to form a GO grafted prepolymer, and finally 1,2-dichloroethane was added to dilute to obtain a standby polyurethane prepolymer, and the chain extender DMTDA was added to the prepolymer and stirred for 2h to form a mixed solution. The prepared mixed solution was slowly poured into a tetrafluoroethylene plate mold, placed in a 30℃ oven, and dried for 12h to solidify into a GAP / GO-ETPU film, which was recorded as ETPU-3.
[0080] Example 8
[0081] 0.2g A-GO and GAP grafted product GO-g-GAP-4 were mixed evenly with GAP polymer as reactive hybrid plasticizer, vacuum dehydrated at 85℃×755mmHg for 1h, cooled to 60℃, and the measured TDI was slowly added to the GAP mixed system, reacted at 75℃ for 2h to form a GO grafted prepolymer, and finally 1,2-dichloroethane was added to dilute to obtain a standby polyurethane prepolymer, and the chain extender DMTDA was added to the prepolymer and stirred for 2h to form a mixed solution. The prepared mixed solution was slowly poured into a tetrafluoroethylene plate mold, placed in a 30℃ oven, and dried for 12h to solidify into a GAP / GO-ETPU film, which was recorded as ETPU-4.
[0082] Example 9
[0083] 0.3g of A-GO and GAP grafted product GO-g-GAP-5 were mixed evenly with GAP polymer as reactive hybrid plasticizer, vacuum dehydrated at 85℃×755mmHg for 1h, cooled to 60℃, and the measured TDI was slowly added to the GAP mixed system, reacted at 75℃ for 2h to form a GO grafted prepolymer, and finally 1,2-dichloroethane was added to dilute to obtain a standby polyurethane prepolymer, and the chain extender DMTDA was added to the prepolymer and stirred for 2h to form a mixed solution. The prepared mixed solution was slowly poured into a tetrafluoroethylene plate mold, placed in a 30℃ oven, and dried for 12h to solidify into a GAP / GO-ETPU film, which was recorded as ETPU-5.
[0084] Example 10
[0085] 0.4g A-GO and GAP grafted product GO-g-GAP-6 were mixed evenly with GAP polymer as reactive hybrid plasticizers, vacuum dehydrated at 85℃×755mmHg for 1h, cooled to 60℃, and the measured TDI was slowly added to the GAP mixed system, reacted at 75℃ for 2h to form a GO grafted prepolymer, and finally 1,2-dichloroethane was added to dilute to obtain a standby polyurethane prepolymer, and the chain extender DMTDA was added to the prepolymer and stirred for 2h to form a mixed solution. The prepared mixed solution was slowly poured into a tetrafluoroethylene plate mold, placed in a 30℃ oven, and dried for 12h to solidify into a GAP / GO-ETPU film, which was recorded as ETPU-6.
[0086] Performance Testing
[0087] The materials obtained in the above-mentioned examples 1 and 2 and the comparative example 1 were subjected to infrared spectroscopy (FT-IR) testing. The testing method is as follows. The results are shown in Figure 4 The materials obtained in Example 3 and Comparative Example 2 were subjected to infrared spectroscopy (FT-IR) testing. The testing method is as follows. The results are shown in Figure 5 .
[0088] Infrared spectrum (FT-IR) test: TENSOR II infrared spectrometer produced by Bruker Optics was used for infrared spectrum analysis. KBr crystal powder tablet method was used to test in a vacuum environment, and the test range was 500-4000cm -1 .
[0089] Depend on Figure 4 It can be seen that the original 3100-3500cm -1 The sharp bands of carboxyl and hydroxyl groups in the range of 2100-2200 cm-1 are transformed into broad and weak stretching vibration bands contributed by the amide NH / ≡CH / OH synergistically. -1 The isolated sharp bands appearing between them are attributed to the characteristic absorption of alkynyl functional groups.
[0090] Depend on Figure 5 It can be seen that as the click reaction occurs, 2100cm -1 The characteristic band of azido group at 1650cm -1 A sharp band appears on the left and right, which is attributed to the joint contribution of the newly formed triazole ring and the vibration of the graphene skeleton.
[0091] The performance tests were performed on the materials obtained in the above comparative examples 5-7 and embodiments 7-10. The test methods are as follows. The results are shown in Table 1.
[0092] Tensile performance test: According to GB / T 16584-1996, AL-7000M uses MZ-4000 tensile testing machine with a tensile rate of 500mm / min to test the mechanical properties.
[0093] Hardness: Tested at 25°C in accordance with GB / T531.1-2008.
[0094] Table 1 Effect of different A-GO contents on the mechanical properties of polyurethane sheets
[0095]
[0096]
[0097] It can be seen from the mechanical property data in Table 1 that after adding GO-g-GAP, the mechanical properties of the prepared GAP / GO-ETPU are greatly improved relative to ETPU-0. Comparative Example 5 is a GAP without A-GO as a reactive hybrid plasticizer. The mechanical properties of the blank polyurethane sheet ETPU-0 are poor. After adding A-GO GAP as a reactive hybrid plasticizer, the mechanical properties of the obtained polyurethane sheet have increased to varying degrees. The mechanical property enhancement effect of the polyurethane sheet obtained in Examples 7-10, where the mass ratio of acetylated graphene oxide to hydroxyl azide glycidyl ether added is 1:10-1:40, is more obvious. As the A-GO content gradually increases during the preparation process of GO-g-GAP, the mechanical property strength of the obtained GAP / GO-ETPU shows a trend of gradually increasing and then decreasing. Among them, the mechanical properties of the polyurethane sheet ETPU-5 obtained in Example 9 are the strongest. Compared with ETPU-0, the hardness is increased by 35.1%, the tensile strength is increased by 106.0%, and the tensile stress is increased by 172.4%. Comparative Example 6 and Comparative Example 7 are polyurethane sheets ETPU-1 and ETPU-2 prepared by adding acetylated graphene oxide and hydroxyl azide glycidyl ether in a mass ratio of 1:10-1:40. The improvement in mechanical properties compared with ETPU-0 is very small and has no practical significance.
Claims
1. A method for preparing alkynylated graphene oxide, characterized in that: The following steps are involved: Ultrasonic dispersion of the carbon material and dimethylformamide to obtain a dispersion; The obtained dispersion liquid was added dropwise with thionyl chloride while stirring, heated in an oil bath, centrifuged after the reaction, washed and dried to obtain Cl-GO; Cl-GO was dispersed with DMF, and acetylenic reactant, dichloromethane and triethylamine were added. After oil bath reaction, centrifugation was performed, and the mixture was washed and dried to obtain acetylenic graphene oxide A-GO.
2. The preparation method according to claim 1, characterized in that: In the preparation of Cl-GO: The carbon material used is selected from one of graphene oxide and carbon nanotubes, preferably graphene oxide, and its carboxyl content is 5wt%; The mass ratio of the added carbon material to dimethylformamide is 1:100-1:500; The oil bath heating temperature is 50-90°C and the reaction time is 18-26h; The drying temperature is 80-150℃, and the drying is carried out under vacuum for 6-8h.
3. The preparation method according to claim 1, characterized in that: In the preparation of A-GO: The alkynyl reactant is selected from any one of pentynol, propynol, and propargylamine; The volume ratio of acetylation reactants: dichloromethane: triethylamine is 1:2:1; The oil bath reaction temperature is 25-60°C and the reaction time is 4-12h.
4. Graphene grafted hydroxyl azide glycidyl ether GO-g-GAP, characterized in that: The alkynyl graphene oxide prepared according to any one of claims 1 to 3 is prepared by click chemistry grafting with hydroxyl azide glycidyl ether.
5. The method for preparing graphene-grafted hydroxyl azide glycidyl ether GO-g-GAP according to claim 4, characterized in that: The following steps are involved: Ultrasonic dispersion of acetylated graphene oxide and dimethylformamide is performed to obtain a dispersion; Hydroxyazide glycidyl ether and a catalyst are added to the dispersion, and the reaction is carried out by heating in an oil bath. The reaction product is centrifuged and dried to obtain graphene-grafted hydroxyazide glycidyl ether GO-g-GAP.
6. The preparation method according to claim 5, characterized in that: The mass ratio of the added alkynylated graphene oxide to hydroxyl azide glycidyl ether is 1:10-1:40; The relative molecular weight of hydroxyazide glycidyl ether is 800-1200.
7. The preparation method according to claim 5, characterized in that: The catalyst is selected from Cu +1 The substance is selected from any one of CuI, CuBr and CuCl; The oil bath heating temperature was 60 °C and the reaction time was 6 h; The drying temperature is 80°C and the drying time is 10 hours.
8. Graphene oxide composite energetic polyurethane elastomer GAP / GO-ETPU, characterized in that: The GO-g-GAP according to claim 4 or the GO-g-GAP prepared according to any one of claims 5 to 7 is added to GAP as a reactive plasticizer to prepare the product.
9. The method for preparing the graphene oxide composite energetic polyurethane elastomer GAP / GO-ETPU according to claim 8, characterized in that: The following steps are involved: GO-g-GAP is added as a filler to hydroxyl azide glycidyl ether, and vacuum dehydration is performed. Toluene diisocyanate is added to the mixed system to react, and then a solvent is added to dilute the mixture. After the reaction is completed, a chain extender is added to react for 1-5 minutes to obtain a mixed solution. The obtained mixed liquid is dried and solidified to obtain GAP / GO-ETPU.
10. The preparation method according to claim 9, characterized in that: The mass ratio of GO-g-GAP and hydroxyazide glycidyl ether added was 1:4; The vacuum dehydration temperature is 75-105°C and the dehydration time is 0.5-1.5h; The prepolymerization temperature is 75-80°C and the reaction time is 1.5-2.5h; The solvent is 1-2-dichloroethane or DMF, and the chain extender is dimethylthiotoluenediamine; The drying temperature is 25℃-40℃.